Report on the 7th scientific meeting of the Association for the Advancement of Young Academics in Neurology (NEUROWIND e.V.) held in Motzen, Germany, October 30–November 1, 2015. (December 2016) - Korn, Thomas; Kleinschnitz, Christoph; Magnus, Tim; Meuth, Sven; Linker, Ralf
Abstract From October 30–November 1, 2015, the 7th NEUROWIND e.V. meeting was held in Motzen, Brandenburg, Germany. Seventy doctoral students and postdocs from over 25 different groups working in German and Swiss University Hospitals or Research Institutes attended the meeting to discuss their latest experiments and findings in the fields of neuroimmunology, neurodegeneration and neurovascular research. This meeting report summarizes the many diverse presentations and the new preclinical to clinical neurology research data that were shared by the participants at the meeting.